INTERACTIVE GAME "POW-POW" TO PROMOTE ENGLISH VOCABULARY LEARNING FOR ELEMENTARY LEARNERS - Bibhuti B Pradhan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Player's experience in the game was considered to be one of the main keys to the game's success. There are several strategies available to improve the interactions of the player in the games. A complex control system is among the unexplored methods using recognition of facial speech. The face expression of the player is captured in real time as the player is playing the game, and the dynamic control system can automatically change the difficulty of the game depending on the facial expressions of the player. This work aims to investigate empirically the application of Facial Expression Recognition to a complex balancing framework increase player experience in the game. Developed and tested two action games (2D and 3D), with 60 respondents in two categories. Both groups played the game twice, one with recognition system of facial expression activated as dynamic balancing, and one without. The findings indicate that there are statistically relevant differences (i.e. improvement) between the baseline and enhanced p < 0.01 games.